2020
DOI: 10.2147/jbm.s252105
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Alpha-Lipoic Acid Supplementation on Cardiovascular Disease Risk Factors in β-Thalassemia Major Patients: A Clinical Trial Crossover Study</p>

Abstract: Aim: Thalassemia is one of the most common genetic diseases, and cardiovascular disease (CVD) has been considered as the leading cause of mortality in more than 50% of β-thalassemia patients. The aim of this study was to determine the effects of alpha-lipoic acid (ALA) on CVD risk factors in β-thalassemia major patients. Methods: Twenty β-thalassemia major patients participated in this randomized crossover clinical trial study. Participants were randomly assigned to ALA (600 mg/day) or placebo groups for two 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The study was conducted with, 9 (30%) female and 21 (70%) male, 30 patients. The mean age of the patients was determined as 10.98±6.30 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years. Other demographic data of study participants are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted with, 9 (30%) female and 21 (70%) male, 30 patients. The mean age of the patients was determined as 10.98±6.30 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years. Other demographic data of study participants are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The hemodynamic effects of blood transfusion are not an area that has been emphasized much. It is known that cardiovascular risks are increased in patients with BTM [12]. These increased risks may be related to the variability of blood pressure in the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Additional 139 papers were excluded due to being pre-print papers ( n = 2), study protocols ( n = 6), reporting data from studies lacking of an appropriate placebo-controlled design for the supplementation ( n = 64), lacking of randomisation ( n = 5), testing the acute effect of ALA supplementation ( n = 7), testing ALA supplementation combined in nutraceutical compounds ( n = 27), testing intravenous treatment with ALA ( n = 11), testing topical treatment with ALA ( n = 4), lacking sufficient information about the nature of the adverse events ( n = 9), or reporting data overlapped with other publications ( n = 4) ( Supplementary file B ). Finally, 71 studies were eligible and included in the systematic review [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Resultsmentioning
confidence: 99%
“…The ability of ALAto reduce the MDAand recycle the glutathione, α‐tocopherol and ascorbic acid has been demonstrated in several studies 16,17 . In addition, our previous studies showed that ALA can decrease a new cardiovascular disease risk factor, ie osteoprotegrin, 18 with no effect on serum iron and total iron binding capacity in thalassemia patients 19…”
Section: Introductionmentioning
confidence: 99%